Implementation of Ecoliteracy and Ecorepreneurship to Grow Entrepreneurial Interest of Science Education Students - Noer Af'idah; Lina Arifah Fitriyah; Oktaffi Arinna Manasikana (Universitas Pendidikan Mandalika, 2021)
This study aimed to foster entrepreneurial interest in Science Education students at Hasyim Asy'ari University through the implementation of ecoliteracy and ecopreneurship in PKLH courses. This research is a type of descriptive research through a qualitative approach wich is carried out as an effort to provide insight and experience to students to reuse waste into quality products and high selling value. This research was conducted during the COVID-19 pandemic through an online system with two stages; first education about the environment (Ecoliteracy) and the second stage in the form of project assignments to manufacture environmental-based entrepreneurial products with waste as the main raw material. The results of the assignment can be used as entrepreneurial product innovations so that students are more creative in producing a product, as well as support one of the government programs to create a healthy and zero waste environment. From this research, it is known that ecoliteracy and ecopreneurship implementation activities can increase students' knowledge about environment; this can be seen from the average pre-test score of 72 to 80 in the post-test and an increase in the percentage of completeness from73% to 100%. Likewise, student interest in entrepreneurship increased, it was showed from the average score of pre-test and post-test 76 to 88. From this activity, student creativity was quite good with an average value 73, this can be seen from the variety of ecopreneurship products produced both from the types of basic materials and products.